Impact of Mohs Micrographic Surgery on Tumor Staging of Cutaneous Squamous Cell Carcinoma: A Comparison of the 7th and 8th Editions of the American Joint Committee on Cancer Guidelines. Issue 8 (August 2018) - Montuno, Michael A.; Brown, Brandon; Konda, Sailesh; Motaparthi, Kiran
Abstract : BACKGROUND: Based on current AJCC-7 guidelines for staging cutaneous squamous cell carcinoma (cSCC), patients with T2 tumor staging represent a prognostically heterogeneous group. The new AJCC-8 guidelines seek to provide improved stratification by inclusion of independent risk factors in the T3 category. These features may be identified in tissue stages during Mohs micrographic surgery (MMS). Thus, low-risk cSCC may be upstaged after MMS, impacting prognosis, additional evaluation, and adjuvant nonsurgical treatment. OBJECTIVE: To examine the impact of MMS on cSCC staging under AJCC-7 and AJCC-8 guidelines. MATERIALS AND METHODS: The medical record was queried for patients who underwent MMS for cSCC. Data were recorded for 190 MMS specimens and corresponding biopsies. Tumor staging according to AJCC-7 and AJCC-8 was assigned. RESULTS: High-risk histologic features are more likely identified with MMS than biopsies. Cutaneous squamous cell carcinoma was equally likely to be upstaged during MMS under both AJCC-7 and AJCC-8, with 10.5% being classified as AJCC-8 T3. Seventy percent of these were only classified as T3 after MMS. Upstaging to T3 during MMS under AJCC-8 is less likely than upstaging to T2 under AJCC-7. CONCLUSION: Mohs surgeons have a significant impact on accurate staging of high-risk cSCC. AJCC-8 improves risk stratification of cSCC.